IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PENERAPAN PROGRAM TUJUH HARI TEMATIK BAGI SISWA SEKOLAH DASAR DI KOTA BEKASI - Siti Auliakhasanah; Wanda Hamidah; Jennyta Caturiasari; Dede Wahyudin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI), 2023)
The development of character education has become something obligation, this is due to being able to create students who are intelligent and have good manners as members of society. Character education carried out in formal institutions is carried out through daily learning that takes place during school, because the values contained in character education are stated in the curriculum which is conveyed explicitly. As is the case with the character education program in the Bekasi area, the point in promoting character education is carried out in an integrated manner in the curriculum. This writing aims to see an overview of the development of character education through the Thematic Seven Days of Education program. In this study, a qualitative type was used with a descriptive analysis method. Data collection techniques were carried out through questionnaires / questionnaires with the acquisition of 24 respondents. From the results of the diagram, it can be concluded that as many as 62% of schools have implemented the Thematic Seven Days of Education program. The program can provide broad freedom for school institutions to develop learning that prioritizes morals according to national identity and personality.